Pengaruh Word of Mouth, Digital Marketing, Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Pada Marketplace Shopee - Wanda Dwi Ramadhan; Ike Kusdyah Rachmawati; Agus Rahman Alamsyah (STIE Wiyatamandala, 2023)
Technology is increasingly coming in and influencing marketing that was previously done with traditional media. The internet is a means for business people to communicate, share information and promote their business. One of the places to buy online is Shopee. Shopee became the top three ranked online shopping app with the highest increase in online shopping demand in Q1 2022. Meanwhile, Shopee is also the most visited application by Indonesians, competing with Lazada and Tokopedia which have been the king of online marketplaces that are most often downloaded on smartphones. This shows that Indonesians today often visit and shop online at Shopee. The purpose of this study is to find out (1) the influence of Word of Mouth on purchasing decisions on the Shopee marketplace, (2) The influence of Digital marketing on purchasing decisions on the Shopee marketplace, (3) The influence of Service Quality on purchasing decisions on the Shopee marketplace. This research method uses a quantitative approach with a total sample of 87 respondents who made more than three purchases. The results of this study show that (1) Word of Mouth has a positive and significant effect on purchasing decisions, (2) Digital Marketing has a positive and significant effect on purchasing decisions, (3) Service Quality has a positive and significant effect on purchasing decisions.